Optimalisasi Sistem Kesiapsiagaan Kebidanan Berbasis Masyarakat Dalam Menghadapi Bencana di Desa Nogosari, Kecamatan Pacet, Kabupaten Pasuruan Provinsi Jawa Timur - Kholifatul Ummah; Theresia Detiati Ngongo; Nisfu Laila (Health Care : Journal of Community Service, 2026)
This community service program aimed to optimize a community-based midwifery preparedness system in Nogosari Village, Pacet District, Pasuruan Regency, East Java, an area with potential natural disaster risks. The target groups included the village midwife, posyandu cadres, disaster volunteers, community leaders, and families responsible for protecting vulnerable groups, particularly pregnant women, women in labor, postpartum mothers, newborns, and toddlers. The methods comprised problem identification through observation and interviews, mapping of high-risk pregnant women, development of preparedness pathways and midwifery standard operating procedures during disasters, cadre training, emergency referral simulation, and evaluation through system readiness monitoring and participant feedback. The results showed the establishment of a Village Midwifery Alert Team, the availability of referral pathways and SOPs, the mapping of high-risk pregnant women, improved cadre ability to recognize pregnancy danger signs, and the availability of a midwifery emergency kit. This program is important because it strengthens cross-sector coordination and improves community readiness to maintain essential midwifery services during disaster situations.